Molecular Assembly Line: Stepwise Hydrogenation of Multifunctional Substrates over Catalyst Mixtures. Issue 3 (14th December 2015) - Tomkins, Patrick; Gebauer‐Henke, Ewa; Müller, Thomas E.
Abstract: The synthesis of many chemical products requires multiple steps. To simplify the overall synthesis by combining consecutive reaction steps, the concept of a "molecular assembly line" promises to yield high reaction rates and selectivities. In this study, mixtures of carbon nanotube (CNT)‐supported catalysts were used to demonstrate the potential of this concept on hand of the hydrogenation of nitrobenzene via aniline to cyclohexylamine. Mixtures of Pt/CNT, having a high activity in nitrobenzene hydrogenation, and of Ru/CNT, highly selective for the hydrogenation of aniline to cyclohexylamine, provided high activity at constant high selectivity. Varying the Pt:Ru ratio to 5:95 was found to be the best case scenario, for which the rates of the two consecutive reaction steps are balanced. The use of catalyst mixtures rather than bimetallic catalysts avoids complex phenomena such as phase separation or migration of one of the metals to the surface of the bimetallic particles. Abstract : Line‐up production concept : The synthesis of many chemical products requires multiple steps. To simplify the overall synthesis by combining consecutive reaction steps, the concept of a "molecular assembly line" promises to yield high reaction rates and selectivities.